INOVASI PENGELOLAAN DANA SIMPAN PINJAM KELOMPOK PEREMPUAN (SPP) PADA UNIT PENGELOLA KEGIATAN (UPK) DI KABUPATEN SUMBAWA - Nudiawati Nudiawati; Farit M. Afendi; M. Budi Setiawan; Dedy Heriwibowo; Zulkieflimansyah Zulkieflimansyah; Arief Budi Witarto (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
The purpose of this research is to know the level of refund Loan Save women's groups (SPP) at Sumbawa district and analyzing the strategy of Innovation management of the Fund Save Loan group of women (SPP) at Sumbawa district. The methods used in this research is quantitative methods that use the approach of the Ex post Facto on the five Subdistrict: Subdistricts of West Base, district, sub-district of Labuhan Badas Utan, Lopok sub district, and Sub-district Lape. The collection of data by the method of observation, kuisioner, documentation and interviews. The results of this study indicate that by doing the Innovation Fund management Save Loan group of women that used to be the level of kolektibilitas above 90% to 43% This means about 47% so an increase in refund the loan. So have significant results to increased kolektibilitas. The conclusion from this study that there are several causes of occurrence of nonperforming loans include: the existence of information that is not true that this is a fund that grants provided by the Government which does not need to be restored, failed harvest, the existence of communities that migrate, and used for other purposes that are urgent.